Canada : Staff Report for the 2007 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2007Article IV Consultation highlights that after surging in the first quarter of 2006, real GDP growth in Canada slowed subsequently, in part reflecting a cooling in the United States. Domestic demand remained the main driver of the economy, with private consumption expanding a robust 3 3/4 percent and business investment growing 8 percent. Financial sector performance remained strong in 2006, largely reflecting continuing benign global market conditions. Long-term interest rates remained low despite monetary tightening, as did spreads on private instruments, reflecting default rates that continue to be low.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet